Effectiveness of online and face-to-face classes : a survey among Malaysian university students for engineering courses - Abdul Hadi Azman,; Muhamad Alias Md. Jedi,; Asma’ Abu Samah,; Muhammad Amin Azman,; Zirour, Mourad; Muhammad Saifuddin Mohamed Rehan,; Mohd Azri Hizami Rasid,; Nor Ashikin Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Since the Movement Control Order was implemented in early 2020, lectures shifted from face-to-face to online classes. Various initiatives were made to improve the experience of online classes. The use of online tools such as Padlet and Kahoot helped in generating interactive sessions and communication between lecturers and students. Some students adapted well to online classes, and some found it less interesting and difficult to follow. Engineering courses require strong understanding of concepts and mathematical calculations. Since the transition to the endemic phases, universities have gradually begun shifting back from online to face-to-face classes. However, online classes has its own advantages, and may be still be conducted in certain cases. Therefore, the aim of this research is to understand students' perception and comparison on the effectiveness of online and face-to-face classes for engineering courses. A survey was conducted among engineering courses from five universities in Malaysia. A total of 255 engineering students participated in the survey. To analyse the data, the methodology used in this paper consists of correlation analysis, the mean correlation coefficient (MCC), multiple regression model and ANOVA. The results show that there are five key factor contributes to the effectiveness and quality in engineering education. In conclusion students satisfied with the effectiveness and quality in engineering education based on five perception questions. The key outcome of this study contributes to the future implementation of online and face-to-face classes for engineering courses in Malaysian universities.